2019
DOI: 10.1177/0887302x19856117
|View full text |Cite
|
Sign up to set email alerts
|

Can Virtually Trying on Apparel Help in Selecting the Correct Size?

Abstract: Close to 30% of garments bought online are returned, often due to issues of fit. These issues often relate to size selection, which is challenging without physically trying on a garment. Alternative methods need to be explored to select the best size in lieu of physically trying apparel on. To address this issue, we compare the size selections based on primary measurements and size charts, virtual garments, and real garments. A cross-sectional quantitative survey was carried out in an experimental setting. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 35 publications
1
7
0
Order By: Relevance
“…Moreover, participants’ VFSs were not significantly different from each other. Therefore, our results supported the past studies’ findings, which showed that the accuracy of the simulations should be improved (Song and Ashdown, 2015; Hernández et al , 2019). Yet, our study findings underlined the subjectivity of the fit notion.…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, participants’ VFSs were not significantly different from each other. Therefore, our results supported the past studies’ findings, which showed that the accuracy of the simulations should be improved (Song and Ashdown, 2015; Hernández et al , 2019). Yet, our study findings underlined the subjectivity of the fit notion.…”
Section: Discussionsupporting
confidence: 92%
“…A UK-only sample was selected in order to investigate RQ2 as, to date, there is limited research investigating body shape classifications within the UK (Grogan et al, 2013). A sample size of 30 was deemed appropriate as not only does it supersede the average sample size used in prior mixed-methods body scanning research (Hernández et al ., 2019) but it is also in line with previous studies that have undertaken semi-structured interviews (Nash, 2019). Participants were not incentivised for taking part in the research.…”
Section: Methodsmentioning
confidence: 99%
“…During a period of 1 month (10 October –13 November, 2018), an online survey was distributed via social media platforms to ascertain the most and least popular dress styles commonly purchased to a convenience sample of 343 UK females, aged 18–34. Dresses were chosen as this type of garment considers key areas of the body (Hernández et al, 2019). Black dresses were selected to minimise the effect of clothing attractiveness, personal preference and fashion trends (Lee & Lee, 2020).…”
Section: Phase 1: Dress Stimuli Selection (Online Dress Survey)mentioning
confidence: 99%